SPEECH FUNCTION AND SPEECH ROLE IN CARL FREDRICKSEN’S DIALOGUE ON UP MOVIE - Ridha Rehana; Sortha Silitonga (State University of Medan, 2013)
Abstract One aim of this article is to show through a concrete example how speech function and speech role used in movie. The illustrative example is taken from the dialogue of Up movie. Central to the analysis proper form of dialogue on Up movie that contain of speech function and speech role; i.e. statement, offer, question, command, giving, and demanding. 269 dialogue were interpreted by actor, and it was found that the use of speech function and speech role. Keywords: movie; speech function; speech role